Flow cytometric detection of chemically induced tandem repeat mutations in two murine cell lines - Healy, Caroline Marie Therese (University of Ottawa (Canada), 2005)
To facilitate detection of genotoxicity from environmental mutagen exposure we generated an in vitro green fluorescence protein (GFP) activation assay that quickly and effectively detects frameshift mutations in tandem repeat sequences (TRS). Two murine cell lines were stably transfected with GFP reporter plasmids in which the GFP constructs contain TRS that shift the GFP coding sequence out of frame. These included several 2-6bp repeat sequences, a control non-repetitive sequence and a human gene sequence with TRS. Transfected cultures were exposed to five model chemicals: hydrogen peroxide (H2O2), 12-O-tetradecanoyl-phorbol-13-acetate (TPA), benzo-a-pyrene-diol-epoxide (BPDE), ethyl nitrosourea (ENU), 9-aminoacridine (9AA). Frameshift mutations resulted in green fluorescent revertants, as determined by flow cytometry and confirmed by sequencing. All five treatments induced a statistically significant sequence- and dose-dependent response in both cell lines. Results from these experiments reveal that the assay responds robustly to various classes of mutagenic substances, as well as carcinogens that are inactive in conventional mutation assays.
Keywords: Biology, Genetics.; Biology, Cell.